Gulag Poetry as Literary Testimony: Poetical and Epistemic Framework - Claudia Pieralli (Studia Litterarum)
The present survey aims at presenting the corpus of verses composed by the victims of рolitical repressions in the Soviet Union from the point of view of published collections and main critical works, concerning, above all, Stalinian era’s texts. At the same time, the study attempts to elaborate and theoretical and epistemic framework within which we can reasonably approach the study of this literary phenomenon of the 20th century Russian history of culture. We deal, first of all, with the possibility of considering these literary texts in relation to the concept of Testimony, and second, with the attempt to highlight specific structural and aesthetical interrelation between the testimonial function and its literary transfiguration in the specific context of poetical creation and expression process. Later, this corpus of texts is regarded as material for the study of the status of poetical word as an aesthetic object which is able to provide a historical (artistic — widely cultural) testimony of Soviet concentration system. Following this assumption, I will outline the literary means and techniques by which the testimonial function is carried out. Within this theoretical framework, the corpus of poetical texts by Soviet political prisoners constitutes a specific whole in the history of the 20th century Russian literature and should be considered as such in the future studies of the subject.